Penerapan Sistem Informasi Website Absensi dengan RFID Berbasis IoT di PT. Eksgon Brother - Tundjungsari, Vitri; Prisdianto, Dendi (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2025)
The expansive number of laborers spread over different offices in a private retail traderequires an proficient time following framework for its workers. This causes teach andinfluences the work execution of each worker. Manual recording and participationframeworks for representatives who are still in utilize result in misplaced time and otherinfringement. Computers are information handling apparatuses that can turn this timeadministration framework into an programmed and valuable framework. In this manner,uncommon information collection is required to record participation and nonattendanceso that work exercises can be recorded precisely and in genuine time. There are numerousways to induce a great time following data framework. One way is to utilize a computerwith a web-based time following application. At PT Eksgon Brother, the framework utilizedwithin the time recording handle is continuously manual and employments a every dayparticipation book, so that it has an affect on the effectiveness and adequacy in collectingand collecting information and its calculation takes a moderately long time. With thechance of blunders and misfortune of participation information is expanding. Based on theover issues, an representative timekeeping data framework was made at PT. EksgonBrother.